A metabolic switch toward lipid use in glycolytic muscle is an early pathologic event in a mouse model of amyotrophic lateral sclerosis. Issue 5 (27th March 2015) - Palamiuc, Lavinia; Schlagowski, Anna; Ngo, Shyuan T; Vernay, Aurelia; Dirrig‐Grosch, Sylvie; Henriques, Alexandre; Boutillier, Anne‐Laurence; Zoll, Joffrey; Echaniz‐Laguna, Andoni; Loeffler, Jean‐Philippe; René, Frédérique
<x xml:space="preserve">Abstract</x> Altered metabolic homeostasis is an early event in amyotrophic lateral sclerosis (ALS) manifestation. This study reveals that skeletal muscles stop using glucose as a source of energy but use lipids instead and this chronic pathologic alteration in muscles is exacerbated with disease progression.